2018
DOI: 10.3390/ijerph15040595
|View full text |Cite
|
Sign up to set email alerts
|

What Persons with Chronic Health Conditions Need to Maintain or Return to Work—Results of an Online-Survey in Seven European Countries

Abstract: Chronic health conditions represent the major share of the disease burden in Europe and have a significant impact on work. This study aims to: (1) identify factors that have a negative or positive impact on the work lives of persons with chronic health conditions; (2) explore the needs of these persons to maintain a job or return to work and (3) compare these results with respect to these persons’ occupational status. An online survey was performed in seven European countries. Open-ended survey questions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 15 publications
1
39
0
1
Order By: Relevance
“…A review of the existing literature on employment and the health status has highlighted that having a long-term chronic disease constitutes a risk factor for not entering the workforce, or for becoming unemployed or non-employed. The results of the PATHWAYS project revealed that the factors having a negative impact for the PwCDs' occupational situation are: workplace, work structure and schedule, as well as workload [44]. A community-based study conducted in the UK provided evidence for longterm diseases and job loss, especially among those who suffer from musculoskeletal disorders and mental illnesses [45].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A review of the existing literature on employment and the health status has highlighted that having a long-term chronic disease constitutes a risk factor for not entering the workforce, or for becoming unemployed or non-employed. The results of the PATHWAYS project revealed that the factors having a negative impact for the PwCDs' occupational situation are: workplace, work structure and schedule, as well as workload [44]. A community-based study conducted in the UK provided evidence for longterm diseases and job loss, especially among those who suffer from musculoskeletal disorders and mental illnesses [45].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the PATHWAYS project showed that a modification of work-related aspects, such as the adaptation of working hours, working tasks and workload, could improve the situation of PwCDs on the labor market [47]. Those work-related aspects correspond to the most frequent needs declared by PwCDs [44]. In turn, national and European stakeholders emphasize the need to focus on the capacity of PwCDs rather than on their inability, as well as to develop a more integrated system of the integration and reintegration of people with NCDs [45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Faced with this evidence, the European PATHWAYS project (www.path-ways.eu), which identified the impact of chronic diseases on European socio-medical systems, has shown how the existing EU and national level legislations regarding inclusive work are not specifically addressed to people with chronic diseases [9][10][11]. Conversely, these legislations apply to specific population groups, such as people with disabilities, long-term unemployed and "fragile" groups, but do not necessarily answer the needs of people affected with one or more chronic diseases [12].…”
Section: Introductionmentioning
confidence: 99%